OPTN-TBK1 axis and a role for PLK1 in HSV-1 infection - Ilina Bhattacharya; Ipsita Volety; Deepak Shukla (mBio, 2023)
ABSTRACTTank-binding kinase 1 (TBK1) plays a pivotal role as a cellular factor in regulating the immune response against herpes simplex virus type 1 (HSV-1). TBK1’s role in defending against HSV-1 is attributed to its capacity to induce the type I interferon response. Recent discoveries emphasize TBK1’s involvement in the regulation of optineurin (OPTN), an autophagy adaptor protein that plays a direct role in enhancing the antiviral response against HSV-1 through selective autophagy. Intriguingly, OPTN can also reciprocally regulate TBK1, leading to a limited understanding of the precise role of the OPTN-TBK1 axis in HSV-1 infection. In our study, we shed light on the relationship between OPTN and TBK1 in influencing the outcome of HSV-1 infection. Surprisingly, when TBK1 or OPTN was absent in cells, the spread and infectivity of HSV-1 did not align as expected. Furthermore, it was unexpected to note that cells lacking OPTN showed higher interferon expression compared to normal cells, yet they exhibited enhanced viral growth. Our investigations revealed that OPTN can directly degrade HSV-1 through autophagy even in the absence of active TBK1. Interestingly, we identified that another protein, Polo-like kinase 1 (PLK1), can compensate for the absence of TBK1 and trigger autophagy to restrict HSV-1. In summary, our findings highlight that OPTN significantly impacts the outcome of HSV-1 infection, regardless of the conventional antiviral response mediated by TBK1. Additionally, by introducing a new role for PLK1, this research provides valuable insights into the intricate interplay among OPTN, TBK1, and autophagy in shaping the course of HSV-1 infection.IMPORTANCEHerpes simplex virus type 1 (HSV-1) is globally prevalent, with latent infections observed in up to 80% of the population. The virus is known for subverting host defense mechanisms and infiltrating the nervous system to establish latency in peripheral ganglia. Multiple stressors can reactivate the virus, and recurrent herpes has been linked to vision loss and neurodegeneration. Identifying critical host factors that limit the spread of HSV-1 and the subsequent establishment of latent infection holds the potential to drive new intervention strategies for eradicating the virus. Numerous pieces of evidence underscore the significance of Tank-binding kinase 1 (TBK1) in restricting HSV-1. Reports have also suggested that phosphorylation of optineurin (OPTN) by TBK1 is required for triggering OPTN-mediated autophagy for HSV degradation. This report adds new insights into the roles of OPTN and TBK1 in HSV-1 infection and provides proof of a TBK1-independent HSV-1 restriction through OPTN. It confirms that TBK1 activation can be substituted by PLK1 to provide protection against HSV-1. In contrast, the activation of OPTN is likely an indispensable host defense mechanism for optimal defense against HSV-1.